2007 IEEE International Electric Machines &Amp; Drives Conference 2007
DOI: 10.1109/iemdc.2007.382727
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the project parameters on the LSRM Project optimization

Abstract: This paper presents the influence of the A. Considerations for the analytical method

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…The dead zone happened when the maximum inductance occurred with no contribution on the generation of propulsion force. The dead zone will be larger with the increase on the absolute difference between the stator and translator pole width [30]. Table 2, it is found that the average thrust force will increase as stator pole width increase until a significant value of 19mm where there is reduction in the average thrust force.…”
Section: Influence Of Stator Pole Width C Pmentioning
confidence: 95%
See 3 more Smart Citations
“…The dead zone happened when the maximum inductance occurred with no contribution on the generation of propulsion force. The dead zone will be larger with the increase on the absolute difference between the stator and translator pole width [30]. Table 2, it is found that the average thrust force will increase as stator pole width increase until a significant value of 19mm where there is reduction in the average thrust force.…”
Section: Influence Of Stator Pole Width C Pmentioning
confidence: 95%
“…In order to increase the efficiency of the actuator, the reduction of the air gap thickness is an alternative method for increasing the propulsion force without affect the actuator dimension [30]. As a general rule, smaller air gap thickness able to produce larger propulsion force.…”
Section: Influence Of Air Gap Gmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, it enforces the company to optimize the available cost for a particular project or only for several projects [7][8] [9]. The above-mentioned issues force the company to manage production cost within particular project optimally [10] [3].…”
Section: Introductionmentioning
confidence: 99%